The expression of FOXP3 in lesions of several forms of leprosy in patients co-infected with HIV - Marília Brasil Xavier; Carla Andréa Avelar Pires; Cláudia Maria de Castro Gomes; Gabriela Fernandes Rodrigues; Débora Pinheiro Xavier; João Augusto Gomes de Souza Monteiro de Brito; Carlos Eduardo Pereira Corbett (Public Library of Science (PLoS), 2021)
Background Brazil remains endemic for infection by the human immunodeficiency virus (HIV) and leprosy, having a major impact on public health and the life quality of affected patients. Although the relevance of this co-infection is recognized, several aspects, such as the immune response, are not yet fully understood. The objective of this study was to investigate the expression of FOXP3+ Treg cells in leprosy skin lesions and to correlate their clinical forms, laboratory characteristics (CD4, CD8, and CV), and the immune reconstitution syndrome in HIV-leprosy co-infection. Methodology/Principal findings An observational, cross-sectional, and analytical study was carried out comparing four groups of patients: those with concomitant diagnosis of leprosy and HIV infection without a leprosy reaction, those with leprosy and HIV co-infection patients with a reverse reaction (RR), those with leprosy without HIV and without reaction, and those with leprosywithout HIV and with RR. The patients were diagnosed at a dermatology outpatient clinic located in Belém, Pará, Brazil, from 2003 to 2017. In the sample studied, there was a positive correlation between FOXP3+ cell density and viral load, negative correlation with blood CD4+ (not statistically significant), significant positive correlation in CD8 count in patients with leprosy reaction, and positive relationship in patients with IRIS. The density of cells expressing FOXP3 was higher in the BL/LL forms in patients without HIV, although the difference was not statistically significant. However, the cell mean was higher in the TT/BT forms in patients co-infected with leprosy and HIV, showing contradictory results. Conclusions/Significance These findings support that higher activity of the HIV may stimulate or result in a higher expression of FOXP3-Tregs and that they may be involved in active immunosuppression observed at the infection site at the tissue level. This supports the need to expand studies on FOXP3+ Treg cells in co-infected patients. Author summary Mycobacterium leprae and the human immunodeficiency virus (HIV) cause infectious diseases that have a major impact on public health worldwide. Both are worrisome diseases, with some knowledge gaps not yet fully clarified, regarding their pathogen biology and clinical evolution, especially when patients are infected with them at the same time. FOXP3 (Forkhead box P3) is a transcription factor present in certain regulatory (CD4+ CD25+) Treg cells, which regulates the immune response of the host during intracellular infections, such as tuberculosis and leishmaniasis. This study aimed to elucidate a few of these gaps by exploring the role of FOXP3-positive regulatory T cells (Tregs) on the immune response during leprosy co-infection with HIV, by comparing the response of patients with leprosy based on whether or not they present a HIV and leprosy reaction. The results showed a positive correlation between FoxP3 + cell density and viral load; negative correlation in relation to blood CD4 +. These findings support the conclusion that a higher activity of HIV may stimulate or result in a higher expression of FOXP3-Tregs. However there is a clear need to expand studies on TregFoxP3 + cells in co-infected patients to further elucidate its role in the pathophysiology of these diseases.